Raja Ravi Varma : the colossus of painting - Hebbāra Illata, Prabhākarana (Abhishek Prakashan, 2009)
On the life and works of Raja Ravi Varma, 1848-1906, famous painter from Kerala, India; includes reproduction of some of his paintings.